The application of Huff spatial model to the development of local living ring in Taiwan, R.O.C. - Tseng, Sheng-bao; Onishi, Takashi; Dias, Hiran D.; Islam, Nazrul; The Government of the Republic of China (Bangkok : Asian Institute of Technology, 1985)
Local Living Ring was adopted by the Government of the Republic of China in its national and regional planning as spatial unit and a measure of eliminating rural-urban disparity problems. To achieve this aim effectively, a rational spatial system to explore the applicability of spatial organization theories, especially Huff Model, in the planning and development of the Local Living Ring in Taiwan, the Republic of China. Using personal computer and its peripheral equipment. a Computer program is developed to draw the spheres of influence of a group of central places. Then putting these theoretical boundaries of each center on the existing administrative boundaries, a theoretical Local living Ring (LLR) can be delineated. The distinctive feature of this study is to make the delineation works faster and more objective. With the replicable processes in mapping and computer work, the planning aspects of analysis and comparison among the alternatives such as different development trends, different time periods, and sectors of different development factors are made more effective and easier. Applying the program to the LLRs system of Taiwan Island, this model and program can delineate the spheres of influence of a group of selected urban centers which are supposed to act as the service centers to their peripheral townships. The past development trend of Taiwan's LLRs are explained clearly through the application of this model/program. The spheres of influence of those local centers are getting smaller and smaller as shown by the figures drawn by the X-Y plotter connected with the personal computer. Since the time distance was not considered in this study, it should be tried in the future study to make the model more realistic.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Regional planning -- Taiwan